Dispensing of psychotropic medication among 400,000 immigrants in The Netherlands - Termorshuizen, Fabian; Selten, Jean-Paul; Heerdink, Eibert R. (Social Psychiatry and Psychiatric Epidemiology, 2017)
Purpose Previously, a high prevalence of certain psychiatric disorders was shown among non-Western immigrants. This study explores whether this results in more prescriptions for psychotropic medication. Methods Data on dispensing of medication among adults living in the four largest Dutch cities in 2013 were linked to demographic data from Statistics Netherlands. Incident (i.e., following no dispensing in 2010–2012) and prevalent dispensing among immigrants was compared to that among native Dutch ( N = 1,043,732) and analyzed using multivariable Poisson and logistic regression. Results High adjusted Odds Ratios (OR adj ) of prevalent and high Incidence Rate Ratios (IRR adj ) of incident dispensing of antipsychotics were found among Moroccan ( N = 115,455) and Turkish individuals ( N = 105,460), especially among young Moroccan males (OR adj = 3.22 [2.99–3.47]). Among Surinamese ( N = 147,123) and Antillean individuals ( N = 41,430), slightly higher rates of dispensed antipsychotics were found and the estimates decreased after adjustment. The estimates for antipsychotic dispensing among the Moroccan and Turkish increased, following adjustment for household composition. Rates for antidepressant dispensing among Turkish and Moroccan subjects were high (Moroccans: OR adj = 1.74 [1.70–1.78]). Among Surinamese and Antillean subjects, the rates for antidepressant dispensing were low and the OR adj lagged behind the IRR adj (Surinamese: 0.69 [0.67–0.71] vs. 1.06 [1.00–1.13]). Similar results were found for anxiolytics. For ADHD medication, lower dispensing rates were found among all migrant groups. Conclusions The findings agree with earlier reports of more mental health problems among Moroccan and Turkish individuals. Surinamese/Antillean individuals did not use psychotropic drugs at excess and discontinued antidepressants and anxiolytics earlier. The data strongly suggest under-treatment for ADHD in all ethnic minority groups.